2022
DOI: 10.1007/s00259-022-05980-w
|View full text |Cite
|
Sign up to set email alerts
|

Human biodistribution and radiation dosimetry of the demyelination tracer [18F]3F4AP

Abstract: Purpose [18F]3F4AP is a novel PET radiotracer that targets voltage-gated potassium (K+) channels and has shown promise for imaging demyelinated lesions in animal models of neurological diseases. This study aimed to evaluate the biodistribution, safety, and radiation dosimetry of [18F]3F4AP in healthy human volunteers. Methods Four healthy volunteers (2 females) underwent a 4-h dynamic PET scan from the cranial vertex to mid-thigh using multiple bed positio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…[ 11 C]3MeO4AP shows low radiation dosimetry based on OLINDA calculation. The effective dose is ∼35 % of [ 18 F]3F4AP (12.2 ± 2.2 μSv/MBq [20], human data) and similar to [ 11 C]choline (4.4 μSv/MBq [21], human data), and [ 11 C]glucose (4.3 μSv/MBq [22], human data). A patient receiving ∼ 400 MBq injection dose of [ 11 C]3MeO4AP will receive ∼ 1.7 mSv of radiation dose from the PET tracer, which is ∼ 1.7 fold of the annual radiation dose limit of individual members of the public (56 FR 23398, May 21, 1991).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 11 C]3MeO4AP shows low radiation dosimetry based on OLINDA calculation. The effective dose is ∼35 % of [ 18 F]3F4AP (12.2 ± 2.2 μSv/MBq [20], human data) and similar to [ 11 C]choline (4.4 μSv/MBq [21], human data), and [ 11 C]glucose (4.3 μSv/MBq [22], human data). A patient receiving ∼ 400 MBq injection dose of [ 11 C]3MeO4AP will receive ∼ 1.7 mSv of radiation dose from the PET tracer, which is ∼ 1.7 fold of the annual radiation dose limit of individual members of the public (56 FR 23398, May 21, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted March 28, 2023. ; https://doi.org/10.1101/2023.03.28.534386 doi: bioRxiv preprint [ 11 C]3MeO4AP is notably lower than the fluorine-18 4AP analogue [ 18 F]3F4AP (measured in human: 12.2 ± 2.2 μSv/MBq [20]; measured in NHPs: 21.6 ± 0.6 μSv/MBq [12]) but comparable to the effective dose of other carbon-11 tracers measured in humans (e.g. [ 11 C]choline: 4.4 μSv/MBq [21], [ 11 C]glucose: 4.3 μSv/MBq [22]) .…”
Section: Biodistribution and Radiation Dosimetry Of [ 11 C]3meo4apmentioning
confidence: 99%
“…Isoflurane anesthesia results in higher [ 18 F]3F4AP brain uptake Recent studies have shown that [ 18 F]3F4AP uptake is markedly different in anesthetized monkeys 10 and awake human subjects 11 . Analysis of reported PET imaging results shows that at corresponds to an SUV90 min-br(NHP) of 1.50 while human imaging studies in awake subjects show an SUV90 min-br(human) of 0.54.…”
Section: Methodsmentioning
confidence: 99%
“…Due to its potential for detecting demyelination this tracer has recently advanced into human studies (clinicaltrials.gov: NCT04699747, NCT04710550). First-in-human imaging with [ 18 F]3F4AP revealed widespread biodistribution and high brain penetration, but also exhibited faster than expected clearance rate and greater metabolism of the radiotracer in blood (less than 50% parent remaining 1h post injection) 11 . Given that the metabolic breakdown of the tracer may lead to a reduced brain uptake, introduce background signal, and create variability across subjects, further studies are warranted.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent findings in humans scanned without anesthesia show that less than 50% parent remains in circulation 1h post intravenous administration (Brugarolas et al 2022) and a study in mice that received [ 18 F]3F4AP awake or under isoflurane showed that non-anesthetized mice readily metabolized the tracer whereas anesthetized animals did not (72±4% vs. 20±5% parent remaining in plasma after 35 min), (Ramos-Torres et al 2022). The observed differences in stability between awake and anesthetized subjects strongly suggest that the high stability in anesthetized animals is mediated by isoflurane.…”
Section: Introductionmentioning
confidence: 99%